2012
DOI: 10.1097/fch.0b013e31824650ed
|View full text |Cite
|
Sign up to set email alerts
|

Salud Sí

Abstract: Participatory evaluation can be an essential tool for community-based organizations in tailoring programs to the needs of the populations they serve. This article provides a case study of Salud Sí, a promotora-driven health promotion program designed to encourage physical activity, fruit and vegetable consumption, and stress reduction among Mexican American women. Through a partnership between a community health center and an academic institution, we describe how the participatory evaluation framework is appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 16 publications
0
12
1
Order By: Relevance
“…Finally, reports on the maintenance of intervention effects and implementation should improve; outcomes after six months, institutionalization of intervention and continuation of delivery should be reported. For instance, Ingram et al, reported physical activity outcomes two years after the program was complete and reported that internal financial resources to continue the program were obtained [60]. …”
Section: Discussionmentioning
confidence: 99%
“…Finally, reports on the maintenance of intervention effects and implementation should improve; outcomes after six months, institutionalization of intervention and continuation of delivery should be reported. For instance, Ingram et al, reported physical activity outcomes two years after the program was complete and reported that internal financial resources to continue the program were obtained [60]. …”
Section: Discussionmentioning
confidence: 99%
“…The articles also demonstrated that CHWs contributed to the community acceptability of interventions, particularly in ensuring the cultural congruence of the intervention and identifying culturally relevant modes of intervention delivery (15, 23, 26, 28-30, 32, 33, 36, 39, 42). CHWs implementing the Salud Sí (Health Yes) intervention were responsible for refining intervention strategies to respond to the needs and characteristics of study participants, such as incorporating spirituality to address depression (26). In other studies, CHWs provided their insights and suggestions to adapt already developed curriculums.…”
Section: Secondary Analysismentioning
confidence: 99%
“…The few studies that involved CHWs in the data interpretation process demonstrated that they were able to explain or validate study findings based on their common experience with the study population (26,35). CHWs in Ingram et al's (26) study explained that women who initiated physical activity during the intervention were able to do so because the program created a culturally acceptable space for women to congregate.…”
Section: Secondary Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…These workers have successfully established intervention programs aimed at decreasing negative consequences of various public health issues 1519 . The promotor de salud is a community leader who provides culturally and linguistically appropriate education to support the advancement of diverse issues.…”
Section: Introductionmentioning
confidence: 99%